Effects of 8 Weeks of Inspiratory Muscle Training on Pulmonary Function and Maximum Inspiratory Pressure and Skill-related Physical Fitness in Women - Dong Seok Kim; Byeong Hwan Jeon (Asian Society of Kinesiology, 2018)
PURPOSE The purpose of this study was verifying effects of 8 weeks of inspiratory muscle training on pulmonary function and maximum inspiratory pressure and skill-related physical fitness in women. METHODS Participants were divided into two group; an inspiratory muscle training group (IMT, n = 8 ) and a placebo control group (CON, n = 8 ). The IMT group carried out inspiratory muscle training six days per week, 30 times a day. 'Paired t-test' for comparison between before and after result in each group. And 'independent sample t-test' for comparison value of before and after result in each groups (SPSS 23.0 Ver.). RESULTS As a results regarding maximum inspiratory pressure, IMT was shown to have a significant effect on peak S-index and peak inspiratory flow(PIF)(p< .001). IMT induced a significant improvement in Sit-up and Shuttle run(p< .01). CONCLUSIONS The results of the present study indicate that IMT is able to improve maximum inspiratory pressure and skill-related physical fitness in women. future studies should attempt to implement variations in methodology including, using male subjects, exercising for a different period of time and evaluating other fitness outcomes.